Reduced CD5 on CD8+ T Cells in Tumors but Not Lymphoid Organs Is Associated With Increased Activation and Effector Function - Alotaibi, Faizah; Vincent, Mark; Min, Wei-Ping; Koropatnick, James (Frontiers in Immunology, 2021)
CD5, a member of the scavenger receptor cysteine-rich superfamily, is a marker for T cells and a subset of B cells (B1a). CD5 associates with T-cell and B-cell receptors and increased CD5 is an indication of B cell activation. In tumour-infiltrating lymphocytes (TILs) isolated from lung cancer patients, CD5 levels were negatively correlated with anti-tumour activity and tumour‐mediated activation-induced T cell death, suggesting that CD5 could impair activation of anti-tumour T cells. We determined CD5 levels in T cell subsets in different organs in mice bearing syngeneic 4T1 breast tumour homografts and assessed the relationship between CD5 and increased T cell activation and effector function by flow cytometry. We report that T cell CD5 levels were higher in CD4+ T cells than in CD8+ T cells in 4T1 tumour-bearing mice, and that high CD5 levels on CD4+ T cells were maintained in peripheral organs (spleen and lymph nodes). However, both CD4+ and CD8+ T cells recruited to tumours had reduced CD5 compared to CD4+ and CD8+ T cells in peripheral organs. In addition, CD5highCD4+ T cells and CD5highCD8+ T cells from peripheral organs exhibited higher levels of activation and associated effector function compared to CD5lowCD4+ T cell and CD5lowCD8+ T cell from the same organs. Interestingly, CD8+ T cells among TILs and downregulated CD5 were activated to a higher level, with concomitantly increased effector function markers, than CD8+CD5high TILs. Thus, differential CD5 levels among T cells in tumours and lymphoid organs can be associated with different levels of T cell activation and effector function, suggesting that CD5 may be a therapeutic target for immunotherapeutic activation in cancer therapy.